Практична реалізація Закону України «Про доступ до публічної інформації» в органах місцевого самоврядування (на прикладі Луцької міської ради) - Бузулук, Ольга С.; Buzuluk, O. S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто, як на практиці реалізований Закон України «Про доступ до публічної інформації» в органах місцевого самоврядування, зокрема, в Луцькій міській раді. Вказано, що дієві механізми реалізації базових інформаційних законів на місцевому рівні ще потрібно виробити. It is considered in the article as in practice law of Ukraine is realized «About access to public information» in the organs of local self-government, in particular, in the Lutsk city council. It is indicated that the effective mechanisms of realization of base informative laws at local level need work. An improvement is required by interpretation of determination of service information as on this soil government bodies attribute to official even that information that before was public at it illegally. At the same time in respect of the Lutsk city council then on results the different monitoring 2011-2013 this government is open and public. The mechanism of practical realization of low can be perfected through realization of seminars, training and lectures on a theme access to public information that will be aimed both at managers and on the recipients of information.
Practical Realization of Low of Ukraine «About Access to Public Information in the Organs of Local Self-Government (on the Example of the Lutsk City Сouncil)
Keywords: закон; law; доступ до інформації; access to information; публічна інформація; public information; органи місцевого самоврядування; organs of local self-government; практична реалізація; practical realization